FRAUD RISK MANAGEMENT UNTUK CV.”X” DI TARAKAN - Vonny Anggelina; Yenny Sugiarti (Perpustakaan Universitas Surabaya, 2018)
The objectives of this research is to explain fraud risk management for CV.”X” in Tarakan in order to detect potential fraud risks that have significant effects for CV.”X”. This research is also to know the proper and appropriate risk management as risk responses for fraud risks in CV.”X”. The sources of data for this research are from interviews, observations and documents analysis. This research use CV.”X” in Tarakan for its object. CV.”X” is a business that sales electronic items. With fraud risk management, we can found potential fraud risks and its proper management for sales and storage activities in CV.”X”. The results from this research are no high fraud risks found in CV.”X”. This research only found medium and low fraud risks. There are 3 fraud risks included in medium risk and there are 7 fraud risks included in low risk. Medium risks in CV.”X” consist of asset misappropriation. Low risks in CV.”X” consist of asset misappropriation and corruption. The responses for the fraud risks are control the risk for another low risks and medium risks, so CV.”X” can minimize their risks.